2012
DOI: 10.1021/ac3013972
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Waveguide Resonance Raman Spectroscopy

Abstract: Raman spectra were collected from a 1.25 M aqueous pyridine solution, 100-nm polystyrene film or a trimethyl(phenyl)silane monolayer at a plasmon waveguide interface under total internal reflection (TIR). The plasmon waveguide resonance (PWR) interface consisted of a sapphire prism/49 to 50 nm Au/548 to 630 nm SiO(2) and a monolayer, thin film or aqueous analyte. The Raman peak area as a function of incident angle was measured using a 785-nm excitation wavelength, and was compared to the Raman peak area obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…Similar trends are observed for sample 3-Bi ( Figure S2A) and sample 3-Tri ( Figure S3A). These representative calculated results suggest that it should be feasible to use SA Raman spectroscopy, with a signal that is proportional to the electric field intensity, [37][38][39][40]49,[53][54][55][56] to measure total film thickness as well as the location of polymer interfaces for both bilayer and trilayer films.…”
Section: Motivation For Determining Buried Interfaces Using Sa Ramamentioning
confidence: 99%
“…Similar trends are observed for sample 3-Bi ( Figure S2A) and sample 3-Tri ( Figure S3A). These representative calculated results suggest that it should be feasible to use SA Raman spectroscopy, with a signal that is proportional to the electric field intensity, [37][38][39][40]49,[53][54][55][56] to measure total film thickness as well as the location of polymer interfaces for both bilayer and trilayer films.…”
Section: Motivation For Determining Buried Interfaces Using Sa Ramamentioning
confidence: 99%
“…Coupled plasmon-waveguide resonance (CPWR) offers a narrower full width half-maximum (FWHM) of the reflective curves that leads to increased precision over conventional surface plasmon resonance (SPR) sensors [14]. Meanwhile, theoretical results indicate that CPWR also results in better performance for both detection range and enhanced electromagnetic field which is highly suitable for dark field excitation of fluorescence to maintain an appreciable sensitivity and signal-to-noise ratio [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Plasmon waveguide resonance (PWR) Raman spectroscopy is a label free spectroscopic method for interfacial analysis with chemical specificity [1][2]. In a standard PWR Raman spectroscopy experiment the illuminating light is directed onto a prism/metal/dielectric/bulk interface at a specific incident angle.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmon waveguides operate by coupling surface plasmon modes in the metal to guided modes within the dielectric layer or waveguide [4]. Recent work has shown that the amplified electric field at a waveguide interface can be used for generating Raman spectra with large signal-to-noise ratios for solutions, polymer films and monolayers [1][2].…”
Section: Introductionmentioning
confidence: 99%